DAMPAK POLA PEMBINAAN POS EKONOMI RAKYAT (PER) TERHADAP KINERJA USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DALAM PENINGKATAN PERTUMBUHAN EKONOMI DAERAH DI KOTA PEKANBARU - Gatot Wijayanto (JIP ( Jurnal Industri dan Perkotaan ), 2011)
This study aimstoanalyze the impact of pattern formation and meniliti People’s Economyof Post (PER) of the level of performance of micro, small and medium enterprises (MSMEs) in order toenhanceregional economic growthin thecity of Pekanbaru and toknow which factors have themost dominantimpactin an effort toimprove theperformance ofsmall and medium enterprisesin enhancingregional economic growthin thecity of Pekanbaru. As for the aspectsinvestigated includedaspects ofcapital, productionandoperations, business management andmarketinginordertoenhanceregional economic growthPekanbaru. The research methodused, namely verification and descriptive, while the population in this study ismicro, small and medium SOE sand partners who have receive dassistance from banking institutions. Using Stratified Random Sampling methodingettingthe sampletomicro, small and medium enterprise stotaling 31 respondents. To determine there lation shipandinfluence of an independent variable onthe dependent variableused in Modelsof MultipleLinearRegressionAnalysis.Meanwhile,totest thehypothesisusingstatistical tests. The results showed that the value of coefficient of determination (R2) equal to 83.34%. This means that approximately 83.34% capital factor, production&operations, business management, and marketing providesa very realimpacton the performance ofmicro, small and medium enterprises (MSMEs) in thecity of Pekanbaru. Partially test showed that the largest value of t-count containedin the production an do peratingvariables, namelyt-count =3.710>ttable =1.667, withthe value of the partial coefficient of determination (r2) =16.63% andp=0.0000. These resultsindicatethatfactorsof production and relate do perations and the most dominant influenceon theperformance ofmicro, small an dmedium enterprises (MSMEs) in thecity of Pekanbaru.